Transparent, flexible graphene–ITO-based neural microelectrodes for simultaneous electrophysiology recording and calcium imaging of intracortical neural activity in freely moving mice - Miao Yuan; Fei Li; Feng Xue; Yang Wang; Baoqiang Li; Rongyu Tang; Yijun Wang; Guo-Qiang Bi; Weihua Pei (Microsystems & Nanoengineering)
Abstract To understand the complex dynamics of neural activity in the brain across various temporal and spatial scales, it is crucial to record intracortical multimodal neural activity by combining electrophysiological recording and calcium imaging techniques. This poses significant constraints on the geometrical, mechanical, and optical properties of the electrodes. Here, transparent flexible graphene–ITO-based neural microelectrodes with small feature sizes are developed and validated for simultaneous electrophysiology recording and calcium imaging in the hippocampus of freely moving mice. A micro-etching technique and an oxygen plasma pre-treating method are introduced to facilitate large-area graphene transfer and establish stable low-impedance contacts between graphene and metals, leading to the batch production of high-quality microelectrodes with interconnect widths of 10 μm and recording sites diameters of 20 μm. These electrodes exhibit appropriate impedance and sufficient transparency in the field of view, enabling simultaneous recording of intracortical local field potentials and even action potentials along with calcium imaging in freely moving mice. Both types of electrophysiological signals are found to correlate with calcium activity. This proof-of-concept work demonstrates that transparent flexible graphene–ITO-based neural microelectrodes are promising tools for multimodal neuroscience research.